Effectiveness of Think–Pair–Share and Peer Tutoring Instructional Strategies on Secondary School Students’ Academic Achievement in Government in Delta State - Anyima, Friday Fidelis; Bassey, Obiageli Ifeoma; Akudolu, Lilian-Rita (Pinisi Journal of Social Science, 2025)
This study investigated the effectiveness of Think-Pair-Share (TPS) and Peer Tutoring instructional strategies on secondary school students’ academic achievement in Government in Delta State, Nigeria. Specifically, it examined the main effects of teaching strategies, gender, and their interaction on students’ performance. A quasi-experimental research design, adopting a pretest-posttest non-equivalent control group structure, was employed. The sample consisted of 180 Senior Secondary Two (SS2) students, selected through multistage sampling from six schools. Three intact classes were assigned to experimental groups (TPS and Peer Tutoring) and a control group (lecture method). The instrument used for data collection was the Government Achievement Test (GAT), which was validated and subjected to a reliability test yielding a coefficient of 0.86 using Kuder-Richardson (KR-20). Data collected were analyzed using mean, standard deviation, and Analysis of Covariance (ANCOVA). Findings revealed that students taught with TPS and Peer Tutoring significantly outperformed their counterparts taught using the lecture method. The study further showed no significant main effect of gender on students’ achievement in Government. Similarly, no significant interaction effect was found between teaching methods and gender on achievement. These findings indicate that TPS and Peer Tutoring are more effective than conventional methods and are equally beneficial to both male and female students. It was recommended that teachers adopt interactive and student-centered methods such as TPS and Peer Tutoring in teaching Government to promote active learning and academic success.